Ctf4 coordinates the progression of helicase and DNA polymerase α - Hirokazu Tanaka; Yuki Katou; Masaru Yagura; Katsuya Saitoh; Takehiko Itoh; Hiroyuki Araki; Masashige Bando; Katsuhiko Shirahige (2009)
Ctf4 is a protein conserved in eukaryotes and a constituent of the replisome progression complex. It also plays a role in the establishment of sister chromatid cohesion. In our current study, we demonstrate that the replication checkpoint is activated in the absence of Ctf4, and that the interaction between the MCM helicase-go ichi ni san (GINS) complex and DNA polymerase alpha (Pol alpha)-primase is destabilized specifically in a ctf4Delta mutant. An in vitro interaction between GINS and DNA Pol alpha was also found to be mediated by Ctf4. The same interaction was not affected in the absence of the replication checkpoint mediators Tof1 or Mrc1. In ctf4Delta cells, DNA pol alpha became significantly unstable and was barely detectable at the replication forks in HU. In contrast, the quantities of helicase and DNA pol epsilon bound to replication forks were almost unchanged but their localizations were widely and abnormally dispersed in the mutant cells compared with wild type. These results lead us to propose that Ctf4 is a key connector between DNA helicase and Pol alpha and is required for the coordinated progression of the replisome.